Aaron Spelling a prime-time life - Spelling, Aaron 1923-2006 (St. Martin's Press, 1996)
The autobiography of the producer of such television shows as "Charlie's Angles" and "Dynasty".
Keywords: Spelling, Aaron; Spelling, Aaron -- 1923-2006; Television producers and directors -- United States -- Biography; Autobiografie; USA; Biografie